Solid films and interfaces in fused salt electrochemical systems - Arvia, Alejandro Jorge (1977)
The present review deals with two main aspects of the electrochemical formation and characteristics of thin solid films. The first shows, through a few typical examples, that these films occur at different metal-molten electrolyte interfaces and that their average composition depends on how they are formed, i.e. anodically or cathodically. The second aspect deals with the kinetics of thin film formation. The first reaction, which has undoubtedly been the more thoroughly investigated, involves the early stages in the formation of an oxygen monolayer on platinum in molten alkali bisulphates. The electrochemical features of this interface are also found at other metal-molten electrolyte interfaces. Finally, the kinetics of multilayer thin film electroformation are presented to show that the nucleation and film growth laws derived for film formation at metal-solution interfaces also apply to metal-melt interfaces.